2022
DOI: 10.3892/ijmm.2022.5132
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin reduces IOP in ocular hypertension in vivo and suppresses ECM in trabecular meshwork perhaps via FGD4

Abstract: To explore the role of atorvastatin in regulating intraocular pressure (IOP) in glaucoma in vivo , and to investigate its related molecular pathway in vitro , an ocular hypertension model was generated by intravitreal injection of an adenoviral vector encoding transforming growth factor (TGF)-β2 in the right eye of BALB/cJ mice, while the left was treated with an empty control adenovirus. To determine its anti-intraocular hypertension role, these induced hyper-IOP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…38,100,101 The proposed mechanism for statins to decrease IOP is by inhibiting the isoprenylation of Rho GTPase thus resulting in decreased actomyosin contractile activity and ECM synthesis/assembly. 39,[102][103][104] All these studies imply that there is an association between lipids, ocular hypertension, and POAG. The data we show clearly suggest that inactivating the SCAP-SREBP pathway decreases TM lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,100,101 The proposed mechanism for statins to decrease IOP is by inhibiting the isoprenylation of Rho GTPase thus resulting in decreased actomyosin contractile activity and ECM synthesis/assembly. 39,[102][103][104] All these studies imply that there is an association between lipids, ocular hypertension, and POAG. The data we show clearly suggest that inactivating the SCAP-SREBP pathway decreases TM lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, even though it is not clear how cholesterol is related to the glaucoma risk, there is mounting evidence showing that HMG‐CoA reductase inhibitor statin can decrease POAG risk by mitigating disease progression 38,100,101 . The proposed mechanism for statins to decrease IOP is by inhibiting the isoprenylation of Rho GTPase thus resulting in decreased actomyosin contractile activity and ECM synthesis/assembly 39,102‐104 . All these studies imply that there is an association between lipids, ocular hypertension, and POAG.…”
Section: Discussionmentioning
confidence: 99%
“…By the same token, lovastatin was shown to cause marked changes in human TM cell morphology including a loss of filamentous (F)-actin stress fiber organization 35 , concomitant with a marked accumulation of cytosolic inactive Rho GTPase proteins 36 . Atorvastatin, another lipophilic statin with higher potency compared to lovastatin 37 , was found to reduce ECM protein expression in human TM cells 38 , as well as induce significant changes in cellular morphology and focal adhesions 39 . Importantly, it was shown that YAP/TAZ activity is controlled by the mevalonate pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, even though it is not clear how cholesterol is related to the glaucoma risk, there is mounting evidence showing that HMG-CoA reductase inhibitor statin can decrease POAG risk by mitigating disease progression (35,86,87). The proposed mechanism for statins to decrease IOP is by inhibiting the isoprenylation of Rho GTPase thus resulting in decreased actomyosin contractile activity and ECM synthesis/assembly (36,(88)(89)(90). All these studies imply that there is an association between lipids, ocular hypertension, and POAG.…”
Section: Discussionmentioning
confidence: 99%